Ultrazvočna preiskava pri diagnosticiranju sarkopenije - Jerele, Cene (Zdravniški vestnik, 2023)
Sarcopenia is defined as age-related loss of muscle mass and function associated with decreased quality of life, increased physical disability, and mortality. Safe, cost-effective, and reliable diagnostic methods are needed for the early diagnosis and treatment of sarcopenia. Ultrasound is an imaging modality increasingly used for the assessment of muscle mass and muscle quality. Using ultrasound parameters, we can predict muscle mass and gain information on muscle tissue quality. Standardized ultrasound imaging protocols can increase the accuracy and reliability of the results. However, the lack of standardized protocols, no clear definition of cut-off values, and sometimes poor correlation of ultrasound parameters with patients’ clinical performance all have a negative impact on the clinical implementation of ultrasound. Nevertheless, with the rapidly growing research, ultrasound is gaining traction in the clinical workup of patients with sarcopenia.
Keywords: mišice; mišična masa; muscle mass; muscle quality; sarcopenia; sarkopenija; ultrasonography; ultrazvočna preiskava